User experience dimensions in product design: a consolidation of what academic researchers know and what design practitioners do. (2015) - BongardBlanchy, Kerstin; Bouchard, Carole; Bonnardel, Nathalie; Lockner, Damien; Aoussat, Améziane
Product design is more than formgiving. This paper gathers design dimensions from academic research and consolidates them with those handled by product designers. The dimensions are extracted from various theoretical models on experience design. To analyse dimensions in product designers' concepts, lexical techniques are employed to obtain keywords that are then classed into design dimensions. We see a good fit between theory and practice. Practice is more precise on dimensions like situational use context and product behaviour. Theory addresses human sensory states, product character as perceived by the user and social use context - dimensions that were missing in the designers- concepts. A compiled dimensions list shows gaps in current design theory and can be a useful tool for design practitioners.